Identifying causes of persistent HIV viremia in adult patients at an academic medical center. (May 2019) - Steinbrink, Julie; Imlay, Hannah; Rao, Krishna; Riddell, James
Objectives: Despite many advances in medicine, not all individuals with HIV are able to achieve complete virologic suppression. This retrospective study identifies variables associated with persistent HIV viremia in an academic clinic. Methods: We studied 66 HIV-infected patients with a viral load of >200 copies/mL over 1 year, with controls matched 1:1 via a propensity score utilizing age at diagnosis, era of diagnosis, gender, and initial CD4 count. We collected data on multiple variables including medications, adherence, comorbidities, hospitalizations, and insurance status. Conditional logistic regression was used for unadjusted and adjusted analyses. Results: A total of 66 viremic cases/matched controls were included. Fewer viremic patients were on antiretroviral therapy for all 12 months (45% vs 77%; odds ratio: 0.33, p = .018) and fewer were of white race (52% vs 70%; odds ratio: 0.49, p = .053). Hospitalization (11% vs 3%; odds ratio: 10, p = .028), underinsurance (20% vs 1%; odds ratio: 5.87, p = .022), and conflicting personal beliefs about their disease (17% vs 3%; odds ratio: 5.5, p = .027) were more common in viremic patients. Psychiatric illness increased the odds of viremia in patients who had four or more visits (odds ratio: 1.63/6.64 with four/five clinic visits, respectively). Conclusion: Psychiatric illness is an important contributor to the presence of persistent viremia in HIV-infected patients and deserves further study.